Rapid and Simultaneous Detection of Salmonella and Campylobacter in Poultry Samples Using Quantum Dots Based Fluorescent Immunoassay Coupled with Magnetic Immunoseparation - Wang , Hong; Li, Yanbin; Slavik, Michael (International Journal of Poultry Science, 2014)
Salmonella Typhimurium and Campylobacter jejuni are the most important bacterial pathogens associated with food borne diseases caused by consuming undercooked poultry or handling raw poultry and poultry products. Because of their low infectious dose of pathogens, a rapid, sensitive, simultaneous detection method is urgently needed. The objective of our research was to develop a sensitive biosensing method for rapid and simultaneous detection of S. Typhimurium and C. jejuni in chicken and ground turkey meat using magnetic nanobeads (MNBs) to capture and separate the target bacteria and quantum dots (QDs) to label the captured bacteria. In this research, both streptavidin conjugated QDs 530 and QDs 620 were coated with the specific biotin conjugated anti-S. Typhimurium and anti-C. jejuni antibodies, respectively. The MNBs were separately coated with the specific biotin conjugated anti-S. Typhimurium and anti-C. jejuni antibodies. The inoculated poultry samples were mixed with conjugated MNBs to capture the two target bacteria. After magnetic immunoseparation, the MNB-cell complexes were mixed with the conjugated QDs 530 and QDs 620 to form the MNB-cell-QD complexes. Unattached conjugated QDs were removed using magnetic separation. Finally, the fluorescence intensities of the MNB-S. Typhimurium-QD and MNB-C. jejuni-QD complexes were measured and correlated to the cell number of two target pathogens. The results showed that S. Typhimurium and C. jejuni in pure culture, chicken carcass and ground turkey wash solutions could be simultaneously separated and detected using the developed immunoassay. The fluorescence intensities at 530 and 620 nm wavelengths increased linearly with the increasing cell numbers of S. Typhimurium and C. jejuni, respectively. The assay detection limit was 30-50 cfu/ml and the assay time was less than 2 h.